Medidas para la reducción de huella de carbono energético en el proceso de impresión flexográfica en la Empresa Imprepack Colombia S.A.S (2022)
The following work presents possible measures to reduce the energy carbon footprint of the equipment used in the flexographic printing process in Bogotá. To begin with, a theoretical framework was made that covers each of the necessary general data, then there is a legal framework which contains information on the regulation of Environmental Management in the city of Bogotá, Colombia. Afterwards, the proposed methodology was executed, which includes visits to the production plant to carry out the different visualization exercises and analysis of machinery, where data on energy consumption per equipment in units of kWh were extracted. Estimated values ​​are 25 kWh for printer 1, 16 kWh for printer 2, 12 kWh for the laminator, 8 kWh for the cutter, 3 kWh for sealer 1, 4 kWh for sealer 2, and 11 kWh for the compressor. This in order to make use of the methodology proposed by the GHG protocol and calculate the energy carbon footprint, fulfilling the objective; Finally, results of the energy carbon footprint are obtained, for this the total energy consumption was calculated, which is 18960 kWh, which generates a carbon footprint of 3116.61 kg CO2eq. Based on these results, different measures are proposed to reduce the same, taking into account the production processes, downtime and corrective and preventive maintenance.